Investigating the effectiveness of STEAM education on students' conceptual understanding of force and energy topics - Ozkan, Gulbin; Umdu Topsakal, Unsal (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2021)
Background An acronym for 'science, technology, engineering, arts, and mathematics,' STEAM education is an approach that supports the understanding of science content by understanding the skills stimulated by artistic experience. However, only a limited number of experimental studies have investigated the effects of STEAM education on concept learning. Therefore, this paper examines the need for STEAM education to focus on the cultivation of students' conceptual understanding of science content. Purpose This study aims to investigate the effectiveness of STEAM education on fostering 7th-grade (aged 13-14 years) students' conceptual understanding of the topics of force and energy. Sample The study sample comprised 74 7th-grade students from two different classes in a Turkish secondary school (study group and control group). Design and Methods An experimental embedded mixed methods design was used, primarily based on quantitative data, with the qualitative data set embedded within and generally playing a supportive role. A control group was used to determine the role of the STEAM approach in the students' conceptual understanding. A STEAM approach was administered to the study group, while the control group was taught according to the regular science curriculum. Research data were collected with the Force and Energy Conceptual Test and through semi-structured interviews with ten study group students. Results The results demonstrate that STEAM education positively affected the students' conceptual understanding and reduced or shifted the number of misconceptions. Furthermore, the study group's post-trial conceptual understanding scores were significantly higher than those of the control group. The interviewees indicated that STEAM education's support for a learner-centered environment fostered the students' conceptual understandings. Conclusions STEAM education is useful for understanding concepts. This study contributes to the literature by investigating the effect of STEAM education approaches on students' conceptual understanding.
Keywords: Conceptual learning; middle-school student; science education; steam; stem; SCIENCE; INTEGRATION; ATTITUDES; TEACHERS; Education & Educational Research